Synergy-building in weather and climate: Partnership between NMHS, policy makers, private sector and media training workshop for Sudan, South Sudan, Uganda and Ethiopia - Abdi, Abduwali (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
CONFER is an EU-funded research project that focuses on climate adaptation through co-production of climate services in East Africa. Its main objective is to co-develop dedicated climate services for the water, energy and food security sectors with stakeholders and end-users, to enhance their ability to plan for and adapt to seasonal climate fluctuations. Thus, it works to reduce disaster risks associated with climate extremes.